Inside Front Cover: Volume 2 Issue 1. (26th March 2021) - Wang, Ning; Miao, Rui Kai; Lee, Geonhui; Vomiero, Alberto; Sinton, David; Ip, Alexander H.; Liang, Hongyan; Sargent, Edward H.
Abstract : Inside front cover image : In the electrocatalytic CO2 reduction devices, especially in flow cell reactors, undesired liquid products crossover from cathode to anode will reduce device productivity and impair the quantitative evaluation of the catalytic performance. The authors reviewed several methods to suppress liquid products crossover including the use of bipolar membranes, solid‐state electrolytes, and cation‐exchange membranes based acidic CO2 R systems. This perspective outlines remaining challenges and prospects to produce concentrated liquid product from CO2 . (DOI: https://doi.org/10.1002/smm2.1018 )